Simultaneous Pancreas and Kidney Transplantation is Associated With Inferior Long-Term Outcomes in African Americans. Issue 1 (January 2018) - Brooks, Joseph T.; Liu, Rong; Oliver, Madeleine; DeLeonibus, Anthony; Mei, Jingning; White, Donald; Siskind, Eric; Ortiz, Jorge
Abstract : Objectives: Simultaneous pancreas and kidney transplant (SPK) is the most effective treatment for patients with type 1 diabetes mellitus and renal failure. However, the effect of ethnicity on SPK outcomes is not well understood. Methods: We studied the influence of recipient ethnicity on SPK using the United Network for Organ Sharing database. A retrospective review of 20, 196 SPK patients from 1989 to 2014 was performed. The recipients were divided into 4 groups: 15, 833 whites (78.40%), 2708 African Americans (AA) (14.39%), 1456 Hispanics (7.21%), and 199 Asians (0.99%). Results: Hispanics and Asians experienced the best overall graft and patient outcomes. Both groups demonstrated significantly superior graft and patient survival rates compared with whites at 1, 3, 5, 10, and 15 years (all P < 0.0001). African Americans experienced significantly superior 1- and 3-year patient survival compared with whites (both P < 0.0001). African Americans also experienced significantly superior 1-year kidney and pancreas graft survival compared with whites ( P < 0.0001). However, AA experienced significantly inferior patient and allograft outcomes for all other time points compared with whites. Conclusions: Based on United Network for Organ Sharing data from 1989 to 2014, AA have worse long-term patient and graft survival rates compared with whites, Hispanics, and Asians undergoing SPK.